2019
DOI: 10.1007/s11263-019-01234-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intentions from Motion: The Subject-Adversarial Adaptation Approach

Abstract: This paper aims at investigating the action prediction problem from a pure kinematic perspective. Specifically, we address the problem of recognizing future actions, indeed human intentions, underlying a same initial (and apparently unrelated) motor act. This study is inspired by neuroscientific findings asserting that motor acts at the very onset are embedding information about the intention with which are performed, even when different intentions originate from a same class of movements. To demonstrate this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Many studies showed that surface electromyography (EMG) signals contain rich information that could be exploited in many fields. They can be used to decode motion intention for recognizing grasping movements [ 4 ] or predicting gait events [ 5 ], and, especially, to understand the neurophysiological mechanisms of motor control [ 6 ]. It was found that the intra-subject variability is crucial in applications involving patients to track the evolution of the disease for diagnosing and treatment planning [ 7 , 8 ] or to assess healthy people’s performance as a reference for motor function evaluation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that surface electromyography (EMG) signals contain rich information that could be exploited in many fields. They can be used to decode motion intention for recognizing grasping movements [ 4 ] or predicting gait events [ 5 ], and, especially, to understand the neurophysiological mechanisms of motor control [ 6 ]. It was found that the intra-subject variability is crucial in applications involving patients to track the evolution of the disease for diagnosing and treatment planning [ 7 , 8 ] or to assess healthy people’s performance as a reference for motor function evaluation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the robot should be able to inform the operator even before she has started to grasps the pipe. In many circumstances, humans are able to infer the motor intention of ongoing goal-directed movements solely based on the observed kinematics of arm and hand [65]. We are currently exploring the application of Deep Neural Networks (DNNs) [38] as a data driven approach to human action recognition and understanding in a manufacturing environment.…”
Section: Discussionmentioning
confidence: 99%
“…These representations may then be used to implement hierarchical processes that predict sensory events. Recent experiments show that DNN architectures may outperform humans in such complex classification tasks like predicting different final intentions of the same class of grasping movements (e.g., grasping for placing or grasping for passing a certain object, [65]). For typical HRI applications, the type of the part or the tool the operator is going to manipulate may help the intention classification (e.g., grasping a screw driver [60]).…”
Section: Discussionmentioning
confidence: 99%
“…They can be used in ON/OFF systems, where a certain movement triggers a control routine to follow a pre-defined trajectory [ 27 ], or use a state-space model to decode the angular velocity of shoulder and motion of elbow [ 28 ]. One can also use position data from the initial portion of a movement to classify motion intention [ 29 ]. Kinematic data can be useful in motion intention detection if the user still has healthy function of their limbs.…”
Section: Introductionmentioning
confidence: 99%